Valuation of Fatal and Non-Fatal Injuries Due to Motorcycle Accidents in Malaysia - Mohd Yusoff, Mohd Faudzi (2006)
Policy makers often struggle with the question of what is the appropriate monetary value to be associated with reduced fatalities. As a result, a disproportionate number of road safety projects were abandoned in favor of other types of projects as they all conlpetc for a limited amount of public funds. This is the motivation for carrying out this research the main objective of which is to evaluate of the value of statistical life (VOSL) of fatal and non-fatal injuries among motorcyclists in Malaysia in an attempt to overcome the lack of reliable estimates of accident. The study utilizes extensively two surveys namely the valuation survey amongst motorcyclists covering 6 constituents within the Seremban Municipality in the state of Negeri Sembilan and the epidemiology survey of hospitalized non-fatal injuries amongst injured motorcyclists at Seremban Hospital to develop the Injury Scale Descriptor. Apart from using descriptive statistics, the inferential statistics have been utilised to test the reliability and stability on the estimated values. Results from the valuation survey passed all the criteria of the construct validity especially the critical scope test. Multiple regression analyses showed statistically significant relationships between WTP and vital variables of income, age, accident experience and riding purpose. A unique variable of race was also found to be significantly related to WTP. Upon control for the effect of inter-country variation in income, the mean values of statistical life (VOSL) have been found to be approximately RM1.1 million and RM77,000 per non-fatal injury. After considering GDP growth, the suggested estimate to reflect the benefits 'of road safety in public policy analysis for year 2004 is RM1.3 million and RM92,400 for fatal and non-fatal injury respectively This study recommends the need for further research on other cost elements to complement the human cost in the effort to establish the comprehensive road accident costs. Other valuation methods should also be conducted in similar valuation studies to fortify the present human cost estimates. Finally, after the successful estimate of intangible benefits (human cost) of road safety, it is strongly recommended that research on other infrastructure investment benefits be undertaken. Only then, can proper Cost Benefit Analysis method become the instrument in evaluating Suture investments of transport infrastructures.